2017
DOI: 10.2217/nnm-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Permeability and Toxicity of Polymeric Nanocapsules Using the Zebrafish Model

Abstract: Beyond the potential value of hyaluronic acid:protamine NCs for overcoming epithelial barriers, this works highlights the utility of zebrafish for fast screening of nanocarriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Zebrafish embryos are robust and can survive different procedures right after fertilization, including genetic manipulation, morpholino [ 73 , 74 , 75 ] or ribonucleoprotein (CRISPR/Cas) [ 76 , 77 , 78 , 79 ] microinjection at single cell stage, as well as cancer cell xenotransplants [ 80 , 81 , 82 , 83 , 84 , 85 ]. In addition, they are transparent, which gives them a definite advantage in many fields of study, because it makes possible, for example, to examine the development of internal structures, and the tracking of the movements and biodistribution of labeled particles (microorganisms, cells, nanoparticles…) in real time [ 85 , 86 , 87 , 88 ]. Visualization can be hampered by the early production of melanin during their embryonic development, as early as 24 hpf (prim5 developmental stage).…”
Section: Zebrafish As a Model Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish embryos are robust and can survive different procedures right after fertilization, including genetic manipulation, morpholino [ 73 , 74 , 75 ] or ribonucleoprotein (CRISPR/Cas) [ 76 , 77 , 78 , 79 ] microinjection at single cell stage, as well as cancer cell xenotransplants [ 80 , 81 , 82 , 83 , 84 , 85 ]. In addition, they are transparent, which gives them a definite advantage in many fields of study, because it makes possible, for example, to examine the development of internal structures, and the tracking of the movements and biodistribution of labeled particles (microorganisms, cells, nanoparticles…) in real time [ 85 , 86 , 87 , 88 ]. Visualization can be hampered by the early production of melanin during their embryonic development, as early as 24 hpf (prim5 developmental stage).…”
Section: Zebrafish As a Model Speciesmentioning
confidence: 99%
“…The two images on top correspond to a zebrafish embryo (left), and to nanometric (~100 nm) lipidic nanoemulsions observed by atomic force microscopy (AFM) (right). Images in the low part of the figure correspond, from left to right, to 48 hpf malformed zebrafish embryo due to toxic effects of nanocapsules (image reproduced with permission from Teijeiro-Valiño et al [ 88 ], fluorescent DiD-labelled lipidic nanoemulsions (blue) injected into the fish circulation system and observed under a fluorescence microscope (images adquired at 48 h post-injection), fluorescent nanoparticles (red) able to extravasate blood vessels (green) in a zebrafish model (image obtained by confocal microscopy by Zou et al [ 133 ], and reproduced with permission), and fluorescent DiD-labelled lipidic nanoemulsions (red) able to interact with cancer cells (green) in xenotransplanted zebrafish embryos (HCT116-GFP) after yolk microinjection.…”
Section: Figurementioning
confidence: 99%
“…Recent studies demonstrated a close correlation between zebrafish and human pigmentation [9][10][11], with many depigmenting agents identified using zebrafish embryos or larvae [12][13][14][15]. In addition, zebrafish are now used to test several types of drug delivery systems, including liposomes [16,17], micelles [18], and nanoparticles [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Despite displaying encouraging effects, the use of curcumin is challenging due to its low solubility in aqueous phase (solubility of <0.5 µg/mL at pH 7.4) and high instability under biologically relevant conditions (pH, light, temperature and oxygen, among others) [ 16 , 19 ]. Vehiculization in oil-in-water (O/W) nanocarriers, as nanoemulsions, has emerged among the interesting strategies used to provide compatibility (solubility or dispersibility) between lipophilic molecules (such as curcumin) and aqueous media [ 20 , 21 ]. Interestingly, several studies have also demonstrated that lipophilic and unstable molecules remain stable within these vehicles, even after being exposed to harsh conditions [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This polymer also has the ability to form gels and hydrophilic structures can be directly included in alginate microgels by mixing the polymeric solution with the selected hydrophilic compound. [ 24 , 25 , 26 , 27 ] Although, it is more difficult to include hydrophobic molecules in such microgels, the use of the previously described O/W nanocarriers allows compatibility of lipophilic molecules within aqueous solvents [ 20 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%